The big five personality characteristics on green HRM banking implementation in Indonesia / Meilaty Finthariasari … [et al.] - Finthariasari, Meilaty; Ranidiah, Furqonti; Islamuddin, Islamuddin; Hermain, Hendra; Rahayu, Sri (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
HR policies in the HR sector must refer to and accommodate the wishes of the HR team and other employees, align with bank policies, principles and civilization, focus on sustainable output to investors, meet customer needs, identify and respond to emerging social trends, respond to government expectations and rigid and manipulating the public policy agenda This study aims to analyze the big five personality variables on green HRM behavior in Indonesian banking. The sample in this study amounted to 395 banking offices spread throughout Indonesia. The data obtained was then processed using the SPSS 21 test tool. Based on the results of the study, the results of the regression test were Y = 7,793 + 0.210X1 + 0.318X2 + 0.138X3 + 0.142X4 + 0.285X5. The results of this study indicate that there is a positive influence between the big five personality variables (Openness, Conscientiousness, Extraversion, Agreeableness, Neuroticism) on Green HRM.